2019
DOI: 10.1111/famp.12506
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Processes in Day‐to‐Day Parent–Adolescent Conflict and Angry Mood: Evidence for Circular Causality

Abstract: Parent-adolescent conflict has been studied both as a precursor of long-term macrolevel developmental risks and as an outcome of microlevel, moment-to-moment interaction patterns. However, the family-level processes underlying the maintenance or regulation of conflict in daily life are largely overlooked. A meso-level understanding of parent-adolescent conflict offers important practical insights that have direct implications for interventions. The present study explores day-today reciprocal processes and carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…Sensitivity analysis revealed that warmth significantly predicted negative affect three but not six hours later. This is in line with daily diary studies, which show inconsistent effects of interaction quality on next-day adolescent well-being (e.g., Boele et al, 2021;LoBraico et al, 2019;Timmons & Margolin, 2015). This highlights the added value of studying interaction quality at several moments within the day, by employing ESM to capture these micro processes.…”
Section: Micro Process Of Parentingsupporting
confidence: 84%
See 2 more Smart Citations
“…Sensitivity analysis revealed that warmth significantly predicted negative affect three but not six hours later. This is in line with daily diary studies, which show inconsistent effects of interaction quality on next-day adolescent well-being (e.g., Boele et al, 2021;LoBraico et al, 2019;Timmons & Margolin, 2015). This highlights the added value of studying interaction quality at several moments within the day, by employing ESM to capture these micro processes.…”
Section: Micro Process Of Parentingsupporting
confidence: 84%
“…However, findings are inconsistent whether parent-adolescent conflict and parental warmth can also predict next day's affect (e.g. Boele et al, 2021;LoBraico et al, 2019;Timmons & Margolin, 2015). Some studies showed substantial effect heterogeneity between families in how interaction quality and adolescent well-being were linked (Borghuis et al, 2020;Chung et al, 2009Chung et al, , 2011Janssen et al, 2020;Timmons & Margolin, 2015).…”
Section: Methods To Study Micro Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The repercussions of interventions and decisions that concern the adolescents make them feel protected and safe in the family context. At this point, they feel understood by their family support network and understand and accept guidance for them to deal with their behaviors, ideas, feelings and are encouraged to make decisions to face life situations (8,10) . Some adolescents mentioned that having a good relationship with their mothers and/or families was a supportive and protective factor against depression and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Current research questions of interest regarding Paths C1 and C2 include the following: (a) How are daily parent‐adolescent emotion dynamics associated with the emergence of longer term patterns? Multivariate multilevel models can be used to examine circular causality with these types of data (e.g., LoBraico, Brinberg, Ram, & Fosco, 2019). (b) How is in‐the‐moment interpersonal emotion regulation, such as responses to each other's emotions, associated with long‐term changes in psychosocial adjustment?…”
Section: Mapping Theory To Methods For Parent‐adolescent Tiesmentioning
confidence: 99%